Literature review: LKPD Berbasis Problem Based Learning (PBL) untuk Meningkatkan Kemampuan Pemecahan Masalah dan Kolaborasi: Literature review: Problem Based Learning (PBL)-Based LKPD to Improve Problem-Solving and Collaboration Capabilities - Sella Arita Reza; Tri Ariani (U-Teach: Journal Education of Young Physics Teacher, 2026)
This literature review aims to examine the effectiveness of Problem-Based Learning (PBL)-based Student Worksheets (LKPD) in enhancing students’ problem-solving abilities and collaboration skills. The review includes 50 articles obtained through the Publish or Perish application and indexed in SINTA 2–4, published between 2015 and 2025, covering various educational levels and fields of study. A qualitative descriptive analysis was employed to identify research patterns, characteristics of LKPD development, and the impact of PBL implementation on 21st-century skills. The findings indicate that PBL-based LKPD consistently received high ratings in terms of validity, practicality, and effectiveness. Most studies reported that PBL-based LKPD is highly feasible for use, based on evaluations by material, language, and media experts. The implementation of PBL syntax comprising problem identification, investigation, information analysis, group discussion, and solution formulation was proven effective in improving students’ critical thinking, problem-solving, and collaboration abilities. The use of authentic problems relevant to real-world contexts also promoted active, participatory, and student-centered learning, aligned with the principles of the Merdeka Curriculum. Overall, this review confirms that PBL-based LKPD is an innovative and relevant instructional tool for developing 21st-century competencies and enhancing the quality of learning in modern educational settings